6m+21=27

Simple and best practice solution for 6m+21=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m+21=27 equation:


Simplifying
6m + 21 = 27

Reorder the terms:
21 + 6m = 27

Solving
21 + 6m = 27

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 6m = 27 + -21

Combine like terms: 21 + -21 = 0
0 + 6m = 27 + -21
6m = 27 + -21

Combine like terms: 27 + -21 = 6
6m = 6

Divide each side by '6'.
m = 1

Simplifying
m = 1

See similar equations:

| X-7=5x+29 | | -2x*x+4x=-1 | | 13n+4n+2n-7n-5n-2=19 | | 5v-4=-29 | | 18y^2/33xy | | 1/10x-1=25 | | 4x*y= | | 9a+15a+-11a+6a=-19 | | 2d+14=2(d-7) | | 4-2n+n=10 | | -8x^4-32x^2=0 | | 7-10s=107 | | 2=m/2-2 | | 6x(x+9)=54 | | 1x+b=c | | 2(5x)=2x+3x+40 | | W^2+10=7w | | x-.15(x)=217 | | 6x+2=2(2x+2) | | -7(3k-7)=196 | | -9(8x-35)=-477 | | 368=r+8(5+5r) | | -2y+6x=12 | | 6w-2=28 | | 8-5(3+8a)=-327 | | 2[a-5]=14 | | 3=9-2c | | 3tg^4x-10tg^2x+3=0 | | 4x+32-2x+16=2 | | 12[3+a]=48 | | 7-6(8x+2)=-293 | | y+11=5y+29 |

Equations solver categories